The influence of ACE genotype on cardiorespiratory fitness of moderately active young men - Almeida, Jeeser Alves (2012)
Background: The angiotensin I-converting enzyme gene (ACE gene) has been broadly studied as for cardiorespiratory fitness phenotypes, but the association of the ACE genotype to middle-distance running has been poorly investigated. Objective: This study investigated the possible influence of Angiotensin-Converting Enzyme (ACE) genotype (I/D) on cardiovascular fitness and middle-distance running performance of Brazilian young males. The validity of VO2max prediction with regard to the ACE genotype was also analyzed. Methods: A homogeneous group of moderately active young males were evaluated in a 1,600 m running track test (V1600m; m.min-1) and in an incremental treadmill test for VO2max determination. Subsequently, the actual and the predicted [(0.177*V1600m) + 8.101] VO2max were compared to ACE genotypes. Results: The VO2max and V1600m recorded for DD, ID and II genotypes were 45.6 (1.8); 51.9 (0.8) and 54.4 (1.0) mL.kg-1. min-1 and 211.2 (8.3); 249.1 (4.3) and 258.6 (5.4) m.min-1 respectively, and were significantly lower for DD carriers (p< 0.05). The actual and predicted VO2max did not differ from each other despite ACE genotype, but the agreement between actual and estimated VO2max methods was lower for the DD genotype. Conclusion: It was concluded that there is a possible association between ACE genotype, cardiovascular fitness and middle-distance running performance of moderately active young males and that the accuracy of VO2max prediction may also depend on the ACE genotype of the participants.